Relationship between ¹²³l-metaiodobenzylguanidine (¹²³l-MIBG) imaging findings and outcome in patients with neuroblastoma at the Red Cross War Memorial Children's Hospital - Amoako, Yaw Ampem (Division of Nuclear Medicine, 2018)
Background: In neuroblastoma, the presence of distant metastases is associated with a poor prognosis. Aim: To assess the relationship between the findings on ¹²³I-MIBG scan and outcome in patients with neuroblastoma at the Red Cross War Memorial Children's Hospital (RCWMCH). Methods: A single observer reviewed the ¹²³I-MIBG scans and clinical data of patients who had a histologically confirmed diagnosis of neuroblastoma and a baseline ¹²³I-MIBG scan and at least one follow up scan after chemotherapy cycles 4 or 7 between January 2001 and May 2015. Follow up extended to June 2016. Disease burden was assessed using the Curie scoring (CS) method. Results: Thirty four stage 4 patients were included in the analysis. Twenty nine (85%) were older than 12 months, with a median age at diagnosis of 32.5 months (range 6 - 93 months). 62% of primary tumours were located in the adrenal gland and half were NMYC amplified. Twenty (59%) patients died, 90% of deaths occurring in patients older than 12 months. No deaths were recorded in the 13 months after recruitment ended. The baseline CS did not predict outcome (alive or dead) or duration of survival. Patients with CS >2 (n = 5) on the cycle 4 scan had a median survival of 19.5 months compared with 29 months for those with a score ≤ 2 (n = 17, p = 0.88). Patients with a CS > 2 on the cycle 7 scan (n = 7) had a median survival of 28 months compared with 35 months for those with CS ≤ 2 (n = 14, p = 0.93). There was no relationship between the magnitude of the decrease in CS between the baseline and post cycle 4 or 7 scans and outcome. Conclusion: In these 34 high risk patients, the baseline CS and CS at cycle 4 or cycle 7 were not significantly indicative of survival. This is similar to other studies that did not find the pre-treatment score or the post treatment MIBG scan to be a predictor of outcome.